Analisis Pengaruh Pandemi Coronavirus Disease 2019 Terhadap Short Term Response Pasar Saham Di Indonesia [Analysis of the Influence of 2019 Coronavirus Disease Pandemic on the Short-Term Response of the Stock Market in Indonesia] - Michael Christofer Tadius (Universitas Pelita Harapan, 2022)
The purpose of the research carried out was to determine the influence of the 2019 coronavirus disease pandemic on the short-term response of the stock market in Indonesia. The Independent Variable used is RMRF. While the dependent variables in the study are JCI, FMS, PRW, and TRANS. The sources collected from this study use secondary data sources in the form of company investment reports, company size based on market cap, and company profitability. The research analysis method uses Eviews 12. The results obtained show that (1) The Coronavirus Disease 2019 pandemic has a negative impact on the brief response of the Indonesian stock market, (2) the Coronavirus Disease 2019 pandemic has put negative pressure on the response of the tourism subsector in Indonesia, (3) the Coronavirus Disease pandemic 2019 has briefly put negative pressure on the pharmaceutical subsector in Indonesia, (4) The pandemic Coronavirus Disease 2019 puts negative pressure on the transportation subsector in Indonesia.BAHASA INDONESIA ABSTRACTTujuan penelitian yang dilakukan adalah untuk mengetahui pengaruh pandemi coronavirus disease 2019 terhadap respon jangka pendek pasar saham di Indonesia. Variabel Independen yang digunakan adalah RMRF. Sedangkan variabel dependen dalam penelitian adalah IHSG, FMS, PRW, dan TRANS. Sumber yang dikumpulkan dari penelitian ini menggunakan sumber data sekunder berupa laporan investasi perusahaan, ukuran perusahaan berdasarkan market cap, dan profitabilitas perusahaan. Metode analisis penelitian menggunakan Eviews 12. Hasil yang diperoleh menunjukkan bahwa (1) Pandemi Coronavirus Disease 2019 memberikan dampak negatif terhadap respon singkat pasar saham Indonesia, (2) Pandemi Coronavirus Disease 2019 memberikan tekanan negatif terhadap respon subsektor pariwisata di Indonesia, (3) Pandemi Coronavirus Disease 2019 memberikan tekanan negatif secara singkat terhadap subsektor farmasi di Indonesia, (4) Pandemi Coronavirus Disease 2019 memberikan tekanan negatif terhadap subsektor transportasi di Indonesia.